A Study of Everyday Aesthetics and (De)Alienation in Wim Wenders’ Alice in the Cities - Zakia Kalam (Sanglap: Journal of Literary and Cultural Inquiry)
This article is a study of Wim Wenders’ Alice in the Cities (1974) where it attempts to explore the aestheticization of everyday images that Wenders weaves into the cinematic narrative of the film. The article examines how the aestheticization renders the everyday as a site of psycho-political transformation through the intertwined relational concept of ‘alienation’ and ‘de-alienation’. In its first section, the article will attempt a discussion of Wenders’ film aesthetics and the dialectical relation of the cinematic and the photographic images central to it. The article will also explore Wenders’ technique of defamiliarization as a method to critically highlight the transformative potential of everyday. In the second section, the article will examine how the everyday experiences generate the psycho-political alienation inevitable under conditions of post-war capitalism and its attendant modernization.  Since this film navigates through different registers of everyday modernity and its impact on the consciousness of its characters, the article will borrow the philosophical insights and sociological approaches of Henri Lefebvre, Walter Benjamin, Georg Simmel who have attempted to theorize the experience of everyday in the context of modernity. It will also follow Nick Malherbe’s political reading of the psychological concept of alienation through a synthesis of the Marxist political praxis and Lacanian psychoanalysis. In the final section the article will investigate the subtle de-alienation that the film maps along the progress in the plot, the character graphs and through its visual regime of the everyday aesthetics in an endeavor to affirm Lefebvre’s hypothesis that the everyday has enormous transformative and emancipatory potential.